Proton pump inhibitors do not increase the risk of dementia: a systematic review and meta-analysis of prospective studies - Desai, Madhav; Nutalapati, Venkat; Srinivasan, Sachin; Fathallah, Jihan; Dasari, Chandra; Chandrasekhar, Viveksandeep Thoguluva; Mohammad, Bilal; Kohli, Divyanshoo; Vaezi, Michael; Katz, Philip O; Sharma, Prateek (Diseases of the esophagus, 2020)
Published studies have reported variable results on the association between duration of proton pump inhibitor (PPI) use and the risk of dementia. An extensive literature search was performed in PubMed, Embase, Google Scholar, and Cochrane for studies examining the risk of cognitive decline and dementia among PPI users versus non-PPI users in prospective studies. Retrospective database linkage studies, case reports, case series, editorials, uncontrolled cohort studies, cross-sectional studies, and review articles were excluded. Primary outcome was pooled hazard rate (HR) of any dementia among PPI users compared with non-PPI users. Secondary outcomes were pooled HR of Alzheimer’s dementia (AD) and risk with long-term PPI follow-up (more than 5 years) studies. Meta-analysis outcomes, heterogeneity (I2), and meta-regression (for the effect of covariates) were derived by statistical software R and Open meta-analyst. A total of six studies (one RCT and five prospective) with 308249 subjects, average age of 75.8 ± 5.2 years, and follow-up of 5 (range 1.5–11) years were included in the analysis. Pooled HR of any dementia was 1.16 (n = 6, 95% confidence interval (CI) = 0.86–1.47). Results remained unchanged when only studies with long-term PPI use (more than 5 years) were analyzed (n = 4, pooled HR 1.10, 95% CI 0.66–1.53). Finally, the pooled HR for AD was 1.06 (n = 3, 95% CI 0.70–1.41). There was substantial heterogeneity among inclusion studies (I2 = 93%). Meta-regression did not demonstrate a significant role of age at study start (P = 0.1) or duration of PPI use (P = 0.62) to incident dementia. The results of this systematic review and meta-analysis do not show a significant relationship between PPI use and dementia in prospective studies with at least a 5-year follow-up.